2014
DOI: 10.1097/01.mnh.0000444815.49755.d9
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for planning the optimal dialysis access for an individual patient

Abstract: A patient-centered approach to the choice of dialysis access that incorporates a balance between recent evidence from the literature and patient preferences may be preferred to the current fistula first focus in vascular access choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Olsha et al demonstrated that 88% of their patients who were older than 80 years had vasculature suitable for autogenous access construction, with patency and complications similar to those of their younger counterparts, with adequate preoperative planning and postoperative maintenance [29]. However, elderly patients with ESRD frequently have a high prevalence of comorbidities, short life expectancy, and poor reported quality of life that is associated with lack of AVF maturation and diminished primary and cumulative AVF patency [28]; in these patients AVG placement might be more beneficial [27, 28, 30]. …”
Section: Introductionmentioning
confidence: 99%
“…Olsha et al demonstrated that 88% of their patients who were older than 80 years had vasculature suitable for autogenous access construction, with patency and complications similar to those of their younger counterparts, with adequate preoperative planning and postoperative maintenance [29]. However, elderly patients with ESRD frequently have a high prevalence of comorbidities, short life expectancy, and poor reported quality of life that is associated with lack of AVF maturation and diminished primary and cumulative AVF patency [28]; in these patients AVG placement might be more beneficial [27, 28, 30]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, supportive care may be another issue for not considering preemptive access in elderly advanced CKD patients. In recent years there has been a concerted emphasis on patient-centered and shared decision making for our elderly advanced CKD patients[13-15], which may impact our thought process when considering pre-emptive vascular access placement in this group. In other words, because dialysis may not confer survival benefit in certain groups of elderly patients with comorbid conditions, excluding them from consideration for preemptive vascular access placement is a reasonable approach.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, catheters have been established as associated with the highest rates of complications, particularly infection (3-10), although they are often needed as a temporary measure, such as until an AV-access (fistula or graft) can be created and used, or as a valid long-term option in select circumstances (11,12). The validity of Fistula First has been recently been challenged in comparisons of outcomes of fistulas and grafts (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, catheters have been established as associated with the highest rates of complications, particularly infection (3-10), although they are often needed as a temporary measure, such as until an AV-access (fistula or graft) can be created and used, or as a valid long-term option in select circumstances (11,12). The validity of Fistula First has been recently been challenged in comparisons of outcomes of fistulas and grafts (12)(13)(14)(15)(16).A systematic review of observational studies comparing clinical outcomes between fistulas and grafts found that the former is associated with high rates of maturation failure but longer-term patency, while the latter is more likely to mature and mature quickly, but with shorter patency (17). The review noted that the included studies are subject to significant risk of bias (17), particularly in the form of selection bias from several sources: 1) patients in whom grafts were placed may have not been eligible for a fistula, as fistulas are generally not created in patients with a shorter life expectancy or significant heart failure (18); 2) patients in whom grafts are placed may have needed a more urgent start on dialysis and therefore may be at greater risk for complications (19), and 3) most of these studies are not analyzed according to the intention-to-treat principle, in other words, they are analyzed by the created access rather than the intended access (20).There are limited studies which detail the costs associated with attaining and maintaining patency of fistulas and grafts (AV-access) among incident and prevalent patients.…”
mentioning
confidence: 99%